Microhomology-Mediated Nonhomologous End Joining Caused Rearrangement of EMD and FLNA in Emery-Dreifuss Muscular Dystrophy - Song, Danyu; Li, Xiaomei; Wei, Wei; Liu, Xueqin; Wu, Lin; Xiong, Hui (Frontiers in Genetics, 2021)
Background: Emery-Dreifuss muscular dystrophy (EDMD) is a rare disease characterized by early joint contractures, slowly progressive muscular dystrophy, and cardiac involvement, which includes arrhythmia, dilated cardiomyopathy, hypertrophic cardiomyopathy, heart failure and sudden death. Methods: Clinical data of the proband and family members were collected. Next-generation sequencing technology was used to analyse the pathogenic variants and copy number variations. Polymerase chain reaction was used to sequence the breakpoints of gene locus rearrangements. Results: Here, we report two siblings with EDMD in a family. The proband, a 17-year-old boy, manifested a dilated right heart, bradycardia, mild muscle weakness and joint contractures. His younger brother only showed a mild bowing limitation with elevated creatine kinase. Next-generation sequencing revealed the complete deletion of EMD and a rearrangement in FLNA (exon29_48dup) in these two patients. The EMD deletion and partial FLNA duplication was accompanied by a 5 bp overlap (GTCCC) on the background of the FLNA-EMD inversion. These findings support the pathogenic mechanism of microhomology-mediated nonhomologous end joining. Conclusion: We report two siblings with complete EMD deletion and FLNA duplication in a family. A microhomology-mediated nonhomologous end joining event involving EMD and FLNA acts as the underlying mechanism.